Laboratory x-ray microscopy using a reflection target system and geometric magnification - Stahlhut, P.; Ebensperger, T.; Zabler, S.; Hanke, R. (Journal of Physics: Conference Series, 2013)
This paper describes a laboratory X-ray microscopy setup, based on geometric magnification. The setup uses a sharp metal tip as a reflection target and a highly focused electron beam of a scanning electron microscope. Here we will describe the structuring process for these metal targets. To demonstrate the capabilities of our system, we show radiographs of test structures corresponding to resolutions below 100nm. There are abilities for 3D imaging in later updates of the system. Further we discuss the first imaging examples for high- and low-absorbing samples.
EAM Import::2019-03-12